EFFICACY OF PGF 2 , CIDR AND OVSYNCH, TREATMENT ON ESTRUS RESPONSE AND FERTILITY RATE IN CROSSBRED COWS - SATHIAMOORTHY, T; KATHIRCHELVAN, M (The Indian Journal of Animal Reproduction, 2023)
A total of three hundred and seventy five postpartum crossbred cows were divided into three groups viz group I, II and Ill. Group I animals (n=180) were treated with PGF2 " after palpation of corpus llJteum. Group II animals (n=155) were treated with CIDR (Controlled Internal Drug Release Device). Group Ill animals (n=40) were treated with ovsynch protocol. Fixed time artificial insemination was performed in the responded animals. Percentage of induced estrus and mean onset of induced estrus were 71.11, 83.20, and 67.50 and 58.8, 44.4, 53.4 hrs in group I, ti and Ill respectively. First service conception rate was 52.20, 42.74 and 55.55 per cent in group I, II and Ill respectively. From this study it may be concluded that Ovsynch treated crossbred cows gave better fertility rate compared to PGF2a and CIDR treated cows.